Muramyl peptide blend ameliorates intestinal inflammation and barrier integrity in cell culture model - D.M. Masiuk; V.S. Nedzvetsky (Gastroenterologìa, 2024)
Background. The intestinal barrier is a crucial structure for maintaining the balance in permeability of digested food and restriction of microbial invasion from internal environment. Imbalance in these functions closely related to the initiation of intestinal epithelium reactivity and inflammation. Inflammation is the most common cause of intestinal dysfunction. Muramyl peptides (MPs) are small signaling molecules which stimulate intracellular receptors of pathogens and are potent regulators of cell response. However, molecular mechanisms of MP effect on intestinal cells remain unknown. The study of MP application to maintain viability of Caco-2 cells was aimed to explore the cytoprotective effect of MP-based probiotic on gut inflammation and intestinal barrier integrity. Materials and methods. Caco-2 cells were treated with 10–100 µg/ml lipopolysaccharide (LPS), 5–50 µg/ml MPs and combination of LPS + MPs. Cell viability was measured with MTT assay. Occludin content was detected with Western blotting. Enzyme-linked immunosorbent assay was applied to assess interleukin-8 (IL-8) production. Results. Obtained results have shown that LPS treatment with doses of 10–100 µg/ml induced in a decrease in cell viability and occludin content. On the contrary, IL-8 content was increased in LPS treatment that evidence the dose-dependent proinflammatory changes in Caco-2 cells. No significant changes were detected in the cells exposed to 5–50 µg/ml doses of MPs. However, application of 50 µg/ml of MPs inhibited IL-8 upregulation in LPS-exposed cells. Besides, MPs exhibited a dose-dependent cytoprotective effect in respect to cell viability at a dose of 20 and 50 µg/ml. Furthermore, MP dose of 50 µg/ml helped restore occludin content in LPS-exposed cells. Conclusions. Taking into the account that occludin is one of major components of tight junctions, MPs can restore epithelial barrier integrity in compromised gut. Observed results demonstrated that MPs is a promising agent in inflammation-induced intestinal injury and maintaining gut barrier function.